FOSTERING TEACHERS’ PROFESSIONAL COMPETENCE THROUGH INTENSIVE COLLABORATIVE WORKSHOP IN CYCLIC LEARNING SYSTEMS - Mantra, Ida bagus Nyoman; Astawa, I Nengah; Rustini, Ni Ketut Pola (Universitas Pendidikan Ganesha, 2019)
Competence is one of the absolute requirements that teachers must have. Having adequate competencies, a teacher will be able to perform his duties as a professional educator and an agent of change. Therefore, education is not only aimed to equip children with various sciences and technology but also variety of life skills. Teachers are professional educators who have been trusted by society to educate and guide children. As a professional educator, a teacher must fulfill teaching requirements that has been regulated. Teachers should have four competences, i.e. pedagogy, personality, professional, and social competence. These competences are needed because the duties and tasks of the teachers to develop their students’ knowledge and skill as well as to build their students’ character. Competent teachers are found to have the ability to develop their students properly as suggested by educational curriculum in order they can survive in facing the global advancement of living.